The Transformation of History Learning in the Digital Age: The Role of Digital Bulletins in Cultivating Students’ Historical Literacy and Historical Thinking - Lobelia Asmaul Husna; Sofiana Afifah Jamil; Nur Fajar Absor; Maisarah; Diki Tri Apriansyah Putra (Jurnal Pendidikan Sejarah, 2026)
Digital transformation has reshaped history education by requiring students not only to acquire historical knowledge but also to develop historical literacy and historical thinking skills. This study aims to analyze the role of a Canva-based digital bulletin in fostering students’ historical literacy and historical thinking within history education in the digital era. The research employed a descriptive qualitative approach conducted at SMAN 84 Jakarta, involving history teachers and students as participants. Data were collected through observations, interviews, and document analysis, and were analyzed using the Miles and Huberman model, which consists of data condensation, data display, and conclusion drawing. Data validity was ensured through source and methodological triangulation. The findings indicate that the digital bulletin helped students understand historical narratives more contextually, increased their interest in reading history, and encouraged them to utilize various historical sources during the learning process. Furthermore, the use of the digital bulletin contributed to the development of historical thinking skills, as reflected in students’ abilities to interpret historical events, analyze cause-and-effect relationships, and understand multiple historical perspectives. The study also revealed a transformation in the roles of teachers and students toward a more student-centered learning environment. Therefore, the Canva-based digital bulletin has the potential to serve as an innovative instructional strategy for 21st-century history education.